Facial, upper facial, and orbital index in Batak, Klaten, and Flores students of Jember University - Masniari Novita (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Forensic anthropology is a neglected branch of physical anthropology in Indonesia. The role of anthropology in forensics including medical and dental forensic is identification. Anthropology could be used in identify skeleton including sex, age, height and race. The aim of this study was to know the facial index, the upper facial index and the orbital index among three different students race population of Jember University used Posteroanterior radiography. The subjects of this study were Batak, Klaten and Flores students of Jember University. The craniometric indices in this study according to the El-Najjar classification. The result showed that all the subjects facial index classified as hypereuryprosopic with the mean between 78.05–79.184. Batak population upper facial index classified as hyperueryene, while Flores and Klaten population were euryene. All the population orbital index classified as hypsiconch.